2011
DOI: 10.3899/jrheum.110360
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Active Disease in Juvenile Idiopathic Arthritis: Sensitivity and Specificity of the Physical Examination vs Ultrasound

Abstract: PE is neither highly sensitive nor specific for identifying active synovitis when compared to US, and screening with US can identify subclinical disease. In joints with both non-bony swelling and limitation of motion with pain on motion or tenderness, and in the knee joint, little additional information is gained by US. This has implications for classification and treatment of JIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 13 publications
(17 reference statements)
4
27
0
3
Order By: Relevance
“…This goes in concordance with the study by Ginger et al (2011)[23], which aimed to determine sensitivity and specificity of the physical examination (PE) for identifying synovitis in the knee and ankle joints of children with JIA. Nineteen patients with JIA were referred for US.…”
Section: Discussionsupporting
confidence: 88%
“…This goes in concordance with the study by Ginger et al (2011)[23], which aimed to determine sensitivity and specificity of the physical examination (PE) for identifying synovitis in the knee and ankle joints of children with JIA. Nineteen patients with JIA were referred for US.…”
Section: Discussionsupporting
confidence: 88%
“…19,32,44 Imaging only-detected disease activity or subclinical synovitis has been shown to correlate with progression of joint damage in adults with rheumatoid arthritis (RA). 45 Magni-Manzoni et al 30 showed that although subclinical synovitis in their cohort of 39 children was common (77%), 67% of children remained in clinical remission after 2 years, concluding that subclinical synovitis does not predict subsequent flare.…”
Section: Disease Activity Assessment and Comparison With Clinical Assmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] It has been suggested that US may be more sensitive in detecting joint inflammation in patients with JIA than the clinical evaluation. [22][23][24][25][26][27] However, the role of US-detected synovitis when clinical manifestations in JIA are absent is unknown. Furthermore, the only published study on the role of US in predicting JIA relapse showed no predictability.…”
Section: Introductionmentioning
confidence: 99%